2012
DOI: 10.1080/01635581.2012.630159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Cancer Preventive Peptide Lunasin by Lactic Acid Bacteria During Sourdough Fermentation

Abstract: This study aimed to exploit the potential of sourdough lactic acid bacteria to release lunasin during fermentation of cereal and nonconventional flours. The peptidase activities of a large number of sourdough lactic acid bacteria were screened using synthetic substrates. Selected lactic acid bacteria were used as sourdough starters to ferment wholemeal wheat, soybean, barley, amaranth, and rye flours. Proteinase activity during fermentation was characterized by SDS-PAGE analysis of the water-soluble extracts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 54 publications
1
55
0
1
Order By: Relevance
“…Bolded peptide masses at m/z 519, 523, 537, 544, 549, 565, 609, 610, 613, 713, and 723 were only found in SDB, therefore, they could be released during sourdough fermentation. Comparing our results with reported SDS-PAGE profiles [28] and peptide content [10,28] of wholemeal wheat sourdoughs fermented by different LAB strains (13.0-22.5 mg/g of Table 2 Proximate composition and GABA content of conventional wheat bread (CB), low-sodium wheat bread (LSB), low-sodium wheat sourdough bread (SDB) and sourdough (SD) Table 2) we found that addition of commercial protease during sourdough fermentation resulted in a more extensive proteolysis and a markedly enrichment of peptides<3 kDa (57.7 mg/g of sourdough d.m.). Peptide concentrations in SDB (11.3 mg/g d.m., Table 2) were slightly lower than the theoretical concentration expected from the addition of SD at a level of 21 % (12.7 mg/g d.m.).…”
Section: Resultssupporting
confidence: 71%
“…Bolded peptide masses at m/z 519, 523, 537, 544, 549, 565, 609, 610, 613, 713, and 723 were only found in SDB, therefore, they could be released during sourdough fermentation. Comparing our results with reported SDS-PAGE profiles [28] and peptide content [10,28] of wholemeal wheat sourdoughs fermented by different LAB strains (13.0-22.5 mg/g of Table 2 Proximate composition and GABA content of conventional wheat bread (CB), low-sodium wheat bread (LSB), low-sodium wheat sourdough bread (SDB) and sourdough (SD) Table 2) we found that addition of commercial protease during sourdough fermentation resulted in a more extensive proteolysis and a markedly enrichment of peptides<3 kDa (57.7 mg/g of sourdough d.m.). Peptide concentrations in SDB (11.3 mg/g d.m., Table 2) were slightly lower than the theoretical concentration expected from the addition of SD at a level of 21 % (12.7 mg/g d.m.).…”
Section: Resultssupporting
confidence: 71%
“…Besides well-known positive effects during food fermentation (e.g., dairy products, fermented meats and leavened baked goods), lactic acid bacteria are recently used to synthesize GABA from grape must [25], isoflavone, aglycones and equol from soy milk, antioxidant and anti-hypertensive peptides, and lunasin from various cereal and pseudo-cereal flours [26,32,33]. Strains of Lactobacillus plantarum , previously isolated from vegetable matrices that are particularly rich of polyphenol compounds [34-36], were used as starters.…”
Section: Discussionmentioning
confidence: 99%
“…Although biological activities such as ACE inhibition and antimicrobial and anticancer activities were reported for cereal peptides (7,8,38,40,41), to the best of our knowledge only a few studies (43) have investigated the potential release of antioxidant peptides during cereal fermentation.…”
mentioning
confidence: 99%